Asupan Natrium dan Kalium sebagai Faktor yang Berhubungan dengan Tekanan Darah pada Pasien Hipertensi - Sadikin, Ilham; Febri, Mustika; Ikhsan, Deri (Journal of Medical and Health Sciences, 2025)
Hypertension remains one of the major health problems in Indonesia, with a prevalence that continues to rise. Dietary factors, particularly sodium and potassium intake, are known to play a crucial role in blood pressure regulation. This study aims to analyze the relationship between sodium and potassium intake and blood pressure in hypertensive patients. The study employed an analytical observational design with a cross-sectional approach. The sample was obtained through purposive sampling of hypertensive patients at primary healthcare facilities. Data on sodium and potassium intake were collected using a 24-hour dietary recall method over three days and analyzed using nutrition analysis software. Blood pressure was measured by trained healthcare professionals using a standard sphygmomanometer. Data were analyzed using Pearson correlation and multiple linear regression tests to determine the strength and direction of the relationships. The results showed a significant positive correlation between excessive sodium intake and increased blood pressure, while low potassium intake was negatively associated with blood pressure among hypertensive patients (p < 0.05). Other factors such as age, body mass index, physical activity, and smoking habits also influenced blood pressure, although their effects were less significant compared to sodium and potassium intake. These findings underscore the importance of dietary interventions as an integral part of hypertension management. In conclusion, controlling sodium intake and increasing the consumption of potassium-rich foods may serve as effective strategies in reducing the risk of hypertension-related complications.